Peran KH Ali Ghazaly dalam Perkembangan Dakwah Persatuan Islam Cianjur Tahun 1960-2003 - Maulana, Ilham; Asep Ahmad Hidayat; Usman Supendi (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
The purpose of this study was to determine the role of KH Ali Ghazaly in the development of the Islamic Unity of Cianjur Da'wah. The type of research used was qualitative research in the form of library research, and in-depth interview techniques with the descendants of KH Ali Ghazaly and other figures who had been involved in the process of developing the Islamic Unity of Cianjur da'wah during the time of KH Aly Ghazaly. The method used was historical research through four stages, namely: heuristic, criticism, interpretation, and historiography. The results of this study are that KH Aly Ghazaly is known as a charismatic cleric, with all his abilities he has brought about the development of the broad da'wah of the Islamic Unity of Cianjur. In addition to being an expert in the field of Hisab science, he is also able to develop the da'wah of the Islamic Unity, and other activities that are programs of the Islamic Unity, especially in Cianjur. Although at that time, the challenges and obstacles in developing the da'wah of the Islamic Unity in Cianjur were very heavy because its existence was still considered taboo by the Cianjur community.